An Eco-Futuristic Approach to Boxing Community Center Design - Andrie Herdiansyah; Gifranza, Gifranza; Imbardi, Imbardi (Journal of Engineering Science and Technology Management, 2025)
The development of urban areas demands the existence of community sports facilities that not only function as physical activity spaces, but also as a medium for shaping environmental quality and the identity of sustainable public spaces. The Boxing Community Center is characterized by high-intensity activities that produce special demands on thermal comfort, air quality, and spatial flexibility. This study aims to examine how an eco-futuristic appropriate is applied in the formation of the Boxing Community Center building mass composition and its implications for environmental performance and architectural expression. The research method used is qualitative-descriptive through literature review, analysis of sports building precedents, and exploration of design concepts. The results of the study show of that the application of fragmented, layered, and climate-adaptive mass composition can improve natural ventilation, daylighting, and the quality of the transition space between the building and the outside environment. In addition to contributing to energy efficiency, this mass composition strategy also creates a dynamic and futuristic architectural image that is in harmony with the character of boxing. This study confirms that the processing of building mass with an eco-futuristic approach plays an important role as a passive strategy as a basis for designing community sports facilities that have optimal environmental performance and long-term flexibility.